Overview and factors associated with pregnancies and abortions occurring in sex workers in Benin - Gentiane Perrault Sullivan; Fernand Aimé Guédou; Georges Batona; Frédéric Kintin; Luc Béhanzin; Lisa Avery; Emmanuelle Bédard; Marie-Pierre Gagnon; Djimon Marcel Zannou; Adolphe Kpatchavi; Michel Alary (BMC, 2020)
Abstract Background Behavioural and structural factors related to sex work, place female sex workers (FSWs) at high risk of maternal mortality and morbidity (MMM), with a large portion due to unintended pregnancies and abortions. In the African context where MMM is the highest in the world, understanding the frequency and determinants of pregnancy and abortion among FSWs is important in order to meet their sexual and reproductive health needs. Methods Data from two Beninese cross-sectional surveys among FSWs aged 18+ (2013, N = 450; 2016, N = 504) were merged. We first performed exploratory univariate analyses to identify factors associated with pregnancy and abortion (p < 0.20) using Generalized Estimating Equations with Poisson regression and robust variance. Multivariate analyses first included all variables identified in the univariate models and backward selection (p ≤ 0.05) was used to generate the final models. Results Median age was 39 years (N = 866). The proportion of FSWs reporting at least one pregnancy during sex work practice was 16.4%, of whom 42.3% had more than one. Most pregnancies ended with an abortion (67.6%). In multivariate analyses, younger age, longer duration in sex work, previous HIV testing, having a boyfriend and not using condoms with him were significantly (p < 0.05) associated with more pregnancies. Conclusion One FSW out of five had at least one pregnancy during her sex work practice. Most of those pregnancies, regardless of their origin, ended with an abortion. Improving access to various forms of contraception and safe abortion is the key to reducing unintended pregnancies and consequently, MMM among FSWs in Benin.